Analisis Kepuasan Masyarakat Terhadap Pelayanan Kantor Camat Siantar Marimbun Menggunakan Algoritma C4.5 - ,; ,; , (Seminar Nasional Informatika (SENATIKA), 2024)
Basically, service has become something that cannot be separated and abandoned in social life. Every community always demands quality services from government officials who provide services. So the author took the initiative to measure the level of public satisfaction with the services provided by the Siantar Marimbun Subdistrict Office, remembering that the author had carried out initial research at the office. For this reason, the C4.5 algorithm is used to assess public satisfaction with the service. There were several problems encountered, such as a lack of human resources at the sub-district office so that some employees held other jobs as well as in the Facilities and Infrastructure section. Infrastructure is also a supporting aspect of community satisfaction. To overcome this problem, the public must provide an assessment to determine the size of public service performance. One method used to determine the quality of service of a public agency is to use the Community Satisfaction Index (IKM). The data collection technique in this research uses a questionnaire which is then processed with the C4.5 algorithm using the RapidMiner application.